Discrimination of Nonobstructive Hypertrophic Cardiomyopathy From Hypertensive Left Ventricular Hypertrophy on the Basis of Strain Rate Imaging by Tissue Doppler Ultrasonography - Kato, Tomoko S.; Noda, Akiko; Izawa, Hideo; Yamada, Akira; Obata, Koji; Nagata, Kohzo; Iwase, Mitsunori; Murohara, Toyoaki; Yokota, Mitsuhiro (Circulation (New York, N.Y.), 2004)
Background— The differentiation of hypertrophic cardiomyopathy (HCM) from hypertensive left ventricular hypertrophy (H-LVH) on the basis of morphological information obtained by conventional echocardiography is occasionally problematic. We investigated whether strain rate (SR) imaging derived from tissue Doppler imaging (TDI) is able to discriminate HCM from H-LVH. Methods and Results— Conventional echocardiography and TDI were performed with 34 patients with LVH and 16 reference subjects. Mean values of systolic strain (ε sys ), peak systolic SR, and early diastolic SR obtained from 8 left ventricular (LV) segments were calculated. LV pressures were recorded simultaneously in the patients. Patients were diagnosed with HCM (n=20) or H-LVH (n=14) on the basis of conventional echocardiography and endomyocardial biopsy findings. Multivariate analysis revealed that septum/posterior wall thickness ratio ( P =0.00013) and ε sys ( P <0.0001) were each able to discriminate HCM from H-LVH. A ε sys cutoff value of −10.6% discriminated between HCM and H-LVH with a sensitivity of 85.0%, specificity of 100.0%, and predictive accuracy of 91.2%. The combination of the septum/posterior wall thickness ratio and ε sys discriminated HCM from H-LVH with a predictive accuracy of 96.1%. The ε sys parameter was significantly correlated with pulmonary arterial wedge pressure, LV end-diastolic pressure, the peak positive first derivative of LV pressure, and the time constant of LV pressure decay. Conclusions— SR imaging is able to discriminate HCM from H-LVH, with ε sys reflecting myocardial contractile and lusitropic properties.